Bacteriophages: Underestimated vehicles of antibiotic resistance genes in the soil - Zhang, Yue; Guo, Yajie; Qiu, Tianlei; Gao, Min; Wang, Xuming (Frontiers in microbiology, 2022)
Bacteriophages (phages), the most abundant biological entities on Earth, have a significant effect on the composition and dynamics of microbial communities, biogeochemical cycles of global ecosystems, and bacterial evolution. A variety of antibiotic resistance genes (ARGs) have been identified in phage genomes in different soil samples. Phages can mediate the transfer of ARGs between bacteria via transduction. Recent studies have suggested that anthropogenic activities promote phage-mediated horizontal gene transfer events. Therefore, the role of phages in the dissemination of ARGs, which are a potential threat to human health, may be underestimated. However, the contribution of phages to the transfer of ARGs is still poorly understood. Considering the growing and wide concerns of antibiotic resistance, phages should be considered a research focus in the mobile resistome. This review aimed to provide an overview of phages as vehicles of ARGs in soil. Here, we summarized the current knowledge on the diversity and abundance of ARGs in soilborne phages and analyzed the contribution of phages to the horizontal transfer of ARGs. Finally, research deficiencies and future perspectives were discussed. This study provides a reference for preventing and controlling ARG pollution in agricultural systems.